Tipologi Ayat Ahl Al-Kitab Dalam Al-Qur’an - Fadhila Sidiq Permana (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2019)
Abstract In the Qur'an the discussion of the Ahl al-Kitab there are many categories. Some contain a condemnation of the Ahl al-book, some of which contain a good expression to the Ahl al-Kitab. What becomes an allergy is that if a person only emphasizes one aspect of the community but the fact that he or she is even crashing into another. A person who only emphasizes the religious community and does not care about other maslahah such as the benefit of the soul (Hifz an-nafs) and common sense (Hifz al-' Aql) will cause various problems in the midst of society. The results concluded that there were five fundamental benefits in the verses relating to the Ahl al-Kitab. Whether it is religious, mental, resourceful, hereditary, or treasure. Then when traced deeper and comparably, there is a relation between one maslahah and other maslahah, such as the recommendation to do justice to the Ahl al-book which was originally an attempt of the Hifz al-'aql turns positive impact For the benefit of the soul (Hifz al-Nafs) and religious benefits (Hifz ad-Din), this is what is then referred to as Maslahah interconnectivity.